Systematic study of Cestode parasite Moniezia (Blanchariezia) Caprae n. sp. of Capra hircus from Kasgi Tq. Omerga Dist. Osmanabad, (MS) India - Kale Sanjay S (International Journal of Life Sciences, 2017)
The new species of the genus moniezia, Blanchard 1891 collected from intestine of Capra hircus at kasgi Tq. Omerga Dist. Osmanabad, M.S india. It differs from all the know species of genus with charactes, scolex small, triangular, auteriorly broad, posteriorly narrow, four suckers towards anterior, oval, long neck, matureproglotttids broader than long, double set of reproductive organs testes 40 to 50 oval, cirrus thin, coiled, protruded within pouch, cirrus pouch near anterior margin of segment, medium cylindrical, curved, thin long vas deferens, ovary bilobed, medium, middle in the segment, vagina thin tube, posterior to cirrus pouch, ootype small, oval, genital pore bilateral, small and oval.